Monetary Policy Rule under Inflation Targeting in Mongolia - Hiroyuki Taguchi; Erdenechuluun Khishigjargal (East Asian Economic Review (EAER), 2018)
This article aims to review the monetary policy rule under inflation targeting framework focusing on Mongolia. The empirical analysis estimates the policy reaction function to see if the inflation targeting has been linked with a monetary policy rule emphasizing on inflation stabilization since its adoption in 2007. The study contributes to the literature by examining the linkage between Mongolian monetary policy rule and inflation targeting directly and thoroughly for the first time and also by taking into account a recent progress in the inflation targeting framework toward forward-looking mode. The main findings were: the Mongolian current monetary policy rule under inflation targeting is characterized as inflation-responsive rule with forward-looking manner (one quarter ahead); the inflation responsiveness is, however, weak enough to be pro-cyclical to inflation pressure; and the rule is also responsive to exchange rate due to the "fear of floating", which weakens the policy reaction to inflation and output gap.
Keywords: E52; E58; O53; 330; Monetary Policy Rule; Inflation Targeting; The Bank of Mongolia; Policy Reaction Function; Fear of Floating